Algorithms in C ++ : parts 1-4; fundamentals data structures sorting searching - Sedgewick, Robert (Delhi : Pearson Education Asia, 1998)
Computer Science
2003-09-02
Keywords: Algorithms - C++; Data structures; Sorting